Fenómeno infobox - Schneider-Schumacher (2003)
Cajas. Infobox Berlín, oficinas de obras y pabellón de información temporaria en Frankfurt, Alemania, año 2000
Keywords: ALEMANIA; FRANKFURT; OFICINAS; SCHUMACHER, MICHAEL